Children’s language in applied linguistic research - Liptakova Ludmila (Južnoslovenski Filolog)
This article is an overview. Its aim is to provide readers with an overview of the most important research on child language development in Slovak, Czech and wider global context. The focus is on research on children’s word formation, within which we are also going to present our own research findings. Children’s linguistic knowledge and abilities are the subject of research in a branch of applied linguistics - developmental linguistics. Within developmental linguistics, subfields focusing on research on child language, such as developmental word formation, are established. Research on child language development also provides useful information for theoretical linguistics, as it points to tendencies in language ontogenesis that can be correlated with dynamic processes in language itself. Knowledge of children’s language is also relevant to educational linguistics, which taps into linguistic research findings to advance language teaching.